Generalized uncertainty principle corrections in Rastall–Rainbow Casimir wormholes - Emmanuele Battista; Salvatore Capozziello; Abdelghani Errehymy (European Physical Journal C: Particles and Fields)
Abstract We explore wormhole solutions sourced by Casimir energy density involving generalized uncertainty principle corrections within the framework of Rastall–Rainbow gravity. The questions of traversability and stability, as well as the presence of exotic matter, are carefully investigated. In particular, the stability issue is addressed via an approach that has not been previously employed in the context of wormholes. This method, which represents an improved version of the so-called Herrera cracking technique, has the potential to yield novel insights in the field of wormhole geometries.